Geotechnical properties of peat soil - Ramli, M.R (Universiti Malaysia Sarawak, UNIMAS, 2009)
Different and excessive settlements are the principal problem confronting engineers working on peat soils. These impose difficult designs and construction conditions, thus it is necessary to know the geotechnical properties of these soils to enable more practical designs to be carried out. Peat and organic soil represent the extreme form of soft soil. They are subject to instability such as sinking and slip failure, and massive primary and long-term settlement when subjected to even moderate load increase. Buildings on peat are usually suspended on piles, but the ground around it may still settle. This study will focus on the properties and consolidation test on peat soils from two areas. Oedometer consolidation test are conducted for both samples taken from Kota Samarahan and Kuching. Several laboratory tests were also conducted for.physical, chemical and engineering properties to determine parameters such as coefficient of consolidation, Cv,,compression index, Cc and coefficient of volume compressibility, mv. Prior to the experimental tests conducted, the result showed the similar deformation for both areas. The coefficient of consolidation, Cv showed decreasing value when subjected to increment of consolidation pressure with time. Meanwhile, the compression index, Cc was found to have a strong correlation between moisture content and void ratio. However, the properties and characteristics of peat varied with their locations and conditions.